2018
DOI: 10.1177/2470547018815901
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Interpersonal Correlates of Suicide Ideation in Military Sexual Trauma Survivors: The National Health and Resilience in Veterans Study

Abstract: Background Veterans who experience military sexual trauma are at increased risk for experiencing suicidal ideation, suicide attempt, and suicide. Yet few studies have attempted to discern factors that relate to suicidal ideation and suicide attempts among survivors of military sexual trauma. The present study aimed to identify psychiatric and interpersonal correlates of suicidal ideation (primary aim) and suicide attempt (secondary aim) among survivors of military sexual trauma. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Veterans with a history of MST (i.e., sexual assault and/or sexual harassment during service) are at elevated risk for suicide. Accordingly, Monteith et al ( 43 ) sought to identify psychiatric and interpersonal correlates of suicidal ideation and suicide attempt among NHRVS veterans with a history of MST. The study found MST survivors who reported more severe alcohol use problems and perceived general disapproval from others in relation to their worst traumatic event were significantly more likely to report current SI and a lifetime suicide attempt; psychological distress was additionally linked to current SI.…”
Section: Suicidalitymentioning
confidence: 99%
“…Veterans with a history of MST (i.e., sexual assault and/or sexual harassment during service) are at elevated risk for suicide. Accordingly, Monteith et al ( 43 ) sought to identify psychiatric and interpersonal correlates of suicidal ideation and suicide attempt among NHRVS veterans with a history of MST. The study found MST survivors who reported more severe alcohol use problems and perceived general disapproval from others in relation to their worst traumatic event were significantly more likely to report current SI and a lifetime suicide attempt; psychological distress was additionally linked to current SI.…”
Section: Suicidalitymentioning
confidence: 99%
“…The relationship between a multitude of traumas, childhood abuse, household dysfunction and the subsequent sequelae of negative medical, psychological, and substance use disorder effects into adulthood was first described with the adverse childhood experiences (ACE) study in the 1990s. 8 Since then, there has been a plethora of empirical studies 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 on a variety of populations looking at the negative health consequences of trauma and exposure to traumatic events across multiple disciplines involving a variety of social determinants of health. For many, psychological injury sets up an already distressed individual to perceive the complex medical system as additionally burdensome, invalidating, and distrustful, exposing them to retraumatization.…”
Section: Introductionmentioning
confidence: 99%